A method for preparing fiber composite photovoltaic bracket material

By adding modified basalt fibers, polyisocyanurate trimers and modified aluminum nitride to the photovoltaic scaffold material, a high-density three-dimensional network structure and thermal conductivity network, the problems of insufficient tensile strength, flame retardant grade and thermal conductivity of photovoltaic scaffold materials in the prior art are solved, and fiber composite photovoltaic scaffold materials with high strength, good flame retardant and excellent thermal conductivity are achieved.

CN119307089BActive Publication Date: 2025-04-15HEBEI JUJIU COMPOSITE MATERIAL CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411841364.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-13
Publication Date
2025-04-15
Estimated Expiration
2044-12-13

AI Technical Summary

Technical Problem

In the prior art, the tensile strength of the photovoltaic bracket material based on epoxy resin is not high, the flame retardant grade is insufficient, and the thermal conductivity is low, which affects the further application of the photovoltaic bracket.

Method used

The fiber composite photovoltaic scaffold material was prepared by adding modified basalt fibers as composite reinforcement material, and then introducing polyisocyanurate trimers and modified aluminum nitride. The material forms a high-density three-dimensional network structure through the combination of modified fibers and polyisocyanurate trimers, which improves the tensile strength and flame retardant properties of the material. At the same time, modifying aluminum nitride builds a thermal conductivity network and improves the thermal conductivity.

Benefits of technology

The high longitudinal tensile strength, good flame retardant performance and improved thermal conductivity of fiber composite photovoltaic support materials are achieved, and the shortcomings of materials in the prior art are solved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The present invention provides a method for preparing a fiber composite photovoltaic bracket material, belonging to the technical field of composite materials. The present invention prepares a fiber composite photovoltaic bracket material by adding modified basalt fiber as a composite reinforcing material, and then introducing polyisocyanurate trimer and modified aluminum nitride. The bracket material has high longitudinal tensile strength and good flame retardant and thermal conductivity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of composite materials, and in particular relates to a method for preparing a fiber composite photovoltaic bracket material. Background Art

[0002] my country's photovoltaic industry is in a stage of rapid development. At present, the photovoltaic brackets used in the photovoltaic industry are mainly steel, which has disadvantages such as high specific gravity and poor corrosion resistance. Fiber composite photovoltaic brackets have excellent properties such as low specific gravity, UV resistance, and corrosion resistance, and are a powerful substitute for traditional metal materials. Basalt fiber composite materials are a composite material with basalt fiber and its products as reinforcing materials and synthetic resin as the matrix material. Basalt fiber has the characteristics of high temperature resistance, acid and alkali resistance, etc. The performance of the reinforced resin is better than that of glass fiber reinforced fiberglass, so it can be used for fiber composite photovoltaic bracket materials.

[0003] A Chinese patent (publication number CN117603474B) discloses a fiber-reinforced unsaturated polyester resin composite material for photovoltaic brackets and its preparation method. The invention uses a synthetic unsaturated polyester oligomer as a matrix material, replaces styrene molecules with acryloylethyl diphenyl phosphate, and then copolymerizes with unsaturated polyester oligomers; on the basis of the above, a carboxyl-terminated butadiene acrylonitrile solution modified with 1,4-butanediol diglycolate and 2-hydroxy-4-glycidyl ether-benzophenone are added to react to obtain a UV-resistant toughened unsaturated polyester solution, and then the fiber-reinforced unsaturated polyester resin composite material for photovoltaic brackets is obtained by pultrusion with basalt fiber and glass fiber. However, the patent does not solve the problems of low tensile strength, insufficient flame retardancy and low thermal conductivity of photovoltaic bracket materials based on epoxy resin in the prior art, which affects the further application of photovoltaic brackets.

[0004] Therefore, how to add fiber materials to photovoltaic bracket materials for compounding, and introduce suitable curing agents and modified components to improve the longitudinal tensile strength of fiber composite photovoltaic bracket materials, and obtain good flame retardant properties and thermal conductivity has become a direction that needs to be focused on. Summary of the invention

[0005] In view of the deficiencies in the prior art, the purpose of the present invention is to provide a method for preparing a fiber composite photovoltaic bracket material, aiming to solve the problems in the prior art of photovoltaic bracket materials based on epoxy resin, such as low tensile strength, insufficient flame retardancy and low thermal conductivity.

[0006] The present invention prepares a fiber composite photovoltaic bracket material by adding modified basalt fiber as a composite reinforcement material, and then introducing polyisocyanurate trimer and modified aluminum nitride. The bracket material has high longitudinal tensile strength and good flame retardant and thermal conductive properties.

[0007] The technical solution adopted by the present invention to solve the above technical problems is as follows:

[0008] The present invention provides a method for preparing a fiber composite photovoltaic bracket material, comprising the following steps:

[0009] Step S1: adding 4 to 6 parts of polyisocyanurate trimer, 2 to 4 parts of aluminum nitride, 0.1 to 0.3 parts of coupling agent, 0.5 to 0.8 parts of film-forming agent and 0.4 to 0.6 parts of lubricant to 85 to 95 parts of liquid polyurethane resin, by weight, and stirring and mixing to obtain a mixture;

[0010] Step S2: Pass 70 to 80 parts of basalt fibers through a mold, inject the mixture in step S1 through a glue injection machine, heat and solidify the mixture, and then pultrude and cool to room temperature to obtain a fiber composite photovoltaic bracket material;

[0011] The preparation method of the polyisocyanurate trimer comprises: mixing and stirring 40-60 parts of polymerized MDI, 3-5 parts of trihydroxy polyether polyol and 5-10 parts of dihydroxy polyether polyol by weight for 20-30 minutes, then adding 0.3-0.5 parts of Bronsted acid catalyst, reacting at 55° C.-65° C. for 2-3 hours under the protection of nitrogen atmosphere to obtain an intermediate product; mixing 40-60 parts of the intermediate product and 20-30 parts of hydroxy polyol for polymerization reaction to obtain a prepolymer system; adding 30-40 parts of trihydroxy polyether polyol to 60-90 parts of the prepolymer system for molding reaction to obtain the polyisocyanurate trimer.

[0012] The following are preferred technical solutions of the present invention, but are not intended to limit the technical solutions provided by the present invention. Through the following preferred technical solutions, the objectives and beneficial effects of the present invention can be better achieved and realized.

[0013] As a preferred technical solution of the present invention, the reaction temperature of the polymerization reaction is 55-65° C., and the reaction time is 2-3 hours.

[0014] As a preferred technical solution of the present invention, the reaction temperature of the molding reaction is 190-200°C, and the reaction time is 25-35s.

[0015] The polyisocyanurate trimer of the present invention undergoes a cross-linking reaction with the hydroxyl groups in the polyurethane resin, thereby increasing the cross-linking density after curing, forming a three-dimensional network structure, and increasing the close bonding between the molecular chains of the resin matrix, thereby increasing the tensile strength of the fiber composite photovoltaic support material; in addition, the polyisocyanurate trimer contains an aromatic ring with high temperature resistance, effectively blocks heat transfer, prevents the spread of flames, and slows down the combustion process. It can delay the thermal decomposition of the material through the endothermic effect, and reduce the generation of combustible gases, thereby increasing the flame retardant performance.

[0016] As a preferred technical solution of the present invention, the basalt fiber is modified basalt fiber;

[0017] The preparation method of the modified basalt fiber comprises: adding 2-4 parts of 2-aminoethyl diphenylborate to 120-150 parts of anhydrous ethanol by weight, stirring for 20-30 minutes to obtain an impregnation solution, adding 50-60 parts of basalt fiber to the impregnation solution for 2-3 hours, and then drying at 100-105° C. for 4-6 hours to obtain the modified basalt fiber.

[0018] After modification, basalt fiber can improve the interfacial bonding strength between it and the matrix resin of photovoltaic bracket materials, and can effectively transfer stress. At the same time, the modified basalt fiber has a better dispersion effect in the composite material. When subjected to external force, it can evenly disperse the stress and prevent material damage caused by local stress concentration. The combined effect improves the longitudinal tensile strength of the photovoltaic bracket material.

[0019] Preferably, the liquid polyurethane resin is any one of a polyether type liquid polyurethane resin, a polyester type liquid polyurethane resin and an oil ether type liquid polyurethane resin, or a combination of at least two of them.

[0020] As a preferred technical solution of the present invention, the aluminum nitride is modified aluminum nitride;

[0021] The preparation method of the modified aluminum nitride comprises: dispersing 10 to 15 parts of aluminum nitride in 90 to 100 parts of anhydrous ethanol by weight, stirring at a speed of 1800 to 2000 r / min for 60 to 80 minutes, then adding 5 to 8 parts of polymethyl methacrylate microspheres and 2 to 4 parts of γ-methacryloxypropyltrimethoxysilane, stirring for 40 to 50 minutes, and filtering to obtain a filter cake; transferring the filter cake to a muffle furnace, keeping the temperature at 130 to 150° C. for 60 to 70 minutes, and then calcining at 450 to 500° C. for 40 to 50 minutes to obtain the modified aluminum nitride.

[0022] The modified aluminum nitride constructs a three-dimensional carbon skeleton network by introducing polymethyl methacrylate and calcining and carbonizing it at high temperature. The three-dimensional carbon skeleton network can provide a dispersed and uniform thermal conduction path; at the same time, the good interface contact between the carbon skeleton and the aluminum nitride particles can effectively transfer heat energy, reduce the interface thermal resistance, and improve the thermal conductivity of the material through a synergistic effect.

[0023] Preferably, the coupling agent is selected from any one of KH550 coupling agent, KH560 coupling agent and KH792 coupling agent, or a combination of at least two thereof.

[0024] Preferably, the film former is an acrylic resin or a polyester polyurethane resin.

[0025] Preferably, the lubricant is selected from any one of cetyltrimethylammonium bromide, cetyltrimethylammonium chloride and octadecyltrimethylammonium chloride, or a combination of at least two thereof.

[0026] Preferably, the conditions of the heating and curing molding process include: a temperature of 190-200° C. and a time of 25-35 seconds.

[0027] Compared with the prior art, the present invention has the following beneficial effects:

[0028] (1) During the high-temperature and long-term curing process, some carbon atoms in the three-dimensional carbon skeleton of modified aluminum nitride migrate and attach to the borate-modified basalt fiber by physical adsorption, forming a continuous thermal conductive network that effectively transfers heat, reduces thermal resistance, and thus increases the thermal conductivity of the fiber composite photovoltaic bracket material.

[0029] (2) The fiber composite photovoltaic bracket material of the present invention introduces aromatic rings by modifying basalt fiber and polyisocyanurate trimer to generate a porous carbonized layer when the material burns, isolating oxygen and heat and preventing further spread of flames. Nitrogen elements can decompose at high temperatures to generate nitrogen oxides or other nitrogen-containing compounds, capture free radicals generated during the combustion process, interrupt chain reactions and inhibit the spread of flames, thereby improving the flame retardant properties of the bracket material.

[0030] (3) After being modified, the basalt fiber of the present invention can improve the interfacial bonding strength between the fiber and the matrix resin of the photovoltaic support material, and can effectively transfer stress. At the same time, the modified basalt fiber has a better dispersion effect in the composite material. When subjected to external force, it can evenly disperse the stress and prevent material damage caused by local stress concentration. The combined effect improves the longitudinal tensile strength of the photovoltaic support material.

[0031] (4) The polyisocyanurate trimer of the present invention can undergo a cross-linking reaction with the hydroxyl groups in the polyurethane resin, thereby increasing the cross-linking density of the polyurethane resin after curing, forming a three-dimensional network structure, and increasing the close bonding between the molecular chains of the resin matrix, thereby increasing the tensile strength of the fiber composite photovoltaic bracket material; in addition, the polyisocyanurate trimer contains an aromatic ring with high temperature resistance, effectively blocking heat transfer, preventing the spread of flames and slowing down the combustion process. It can delay the thermal decomposition of the material through endothermic action and reduce the generation of combustible gases, thereby increasing the flame retardant properties.

[0032] (5) The modified aluminum nitride of the present invention constructs a three-dimensional carbon skeleton network by introducing polymethyl methacrylate and calcining and carbonizing at high temperature. The three-dimensional carbon skeleton network can provide a dispersed and uniform heat conduction path; at the same time, the good interface contact between the carbon skeleton and the aluminum nitride particles can effectively transfer heat energy, reduce the interface thermal resistance, and improve the thermal conductivity of the material through a synergistic effect. DETAILED DESCRIPTION

[0033] For the convenience of understanding the present invention, the present invention lists the following embodiments. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0034] The sources of some components in the embodiments and comparative examples are as follows:

[0035] Polymeric MDI, product number BS293, was purchased from Wanhua Chemical Group Co., Ltd.;

[0036] Trihydroxy polyether polyol, product number TEP-330N, purchased from Shanghai Kaiyin Chemical Co., Ltd.;

[0037] Dihydroxy polyether polyol, product number N210, purchased from Sangda Chemical (Nantong) Co., Ltd.;

[0038] Hydroxypolyol, product number CYD-P214, was purchased from Weihai Chenyuan Molecular New Materials Co., Ltd.;

[0039] Commercially available basalt fiber, item number FD2706, was purchased from Shandong Oude Chemical Fiber Products Co., Ltd.;

[0040] Polyether type liquid polyurethane resin, model HY5104L-D, purchased from Hebei Jujiu Composite Materials Co., Ltd.;

[0041] Polyester type liquid polyurethane resin, model HY5104L-S, purchased from Hebei Jujiu Composite Materials Co., Ltd.;

[0042] Oil ether type liquid polyurethane resin, model HY5104L-A, purchased from Hebei Jujiu Composite Materials Co., Ltd.;

[0043] Commercially available aluminum nitride, product number XH-AlN-30, was purchased from Shanghai Xiaohuang Nanotechnology Co., Ltd.;

[0044] KH550 coupling agent, CAS No. 919-30-2, purchased from Shanghai Yuanye Biotechnology Co., Ltd.;

[0045] KH560 coupling agent, CAS No. 2530-83-8, purchased from Shanghai Yuanye Biotechnology Co., Ltd.;

[0046] KH792 coupling agent, CAS No. 1760-24-3, purchased from Hubei New Blue Sky New Materials Co., Ltd.;

[0047] Acrylic resin, model THYOSIL E1560, purchased from Qingdao Linke Industry and Trade Co., Ltd.;

[0048] Polyester polyurethane resin, brand name Texin260, sourced from Shanghai Institute of Organic Chemistry, Chinese Academy of Sciences;

[0049] Hexadecyltrimethylammonium bromide, CAS No. 57-09-0, purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.;

[0050] Hexadecyltrimethylammonium chloride, CAS No. 112-02-7, purchased from Shanghai Jizhi Biochemical Technology Co., Ltd.;

[0051] Octadecyltrimethylammonium chloride, CAS No. 112-03-8, purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.;

[0052] 2-Aminoethyl diphenylborate, CAS No. 524-95-8, purchased from Sinopharm Chemical Reagent Co., Ltd.;

[0053] Bronsted acid catalyst, product number 357537, purchased from Shanghai MacLean Biochemical Technology Co., Ltd.;

[0054] Anhydrous ethanol, CAS No. 64-17-5, was purchased from Sinopharm Chemical Reagent Co., Ltd.;

[0055] Polymethyl methacrylate microspheres, catalog number ZZS-MMA1000, were purchased from Shanghai Zhenzhun Biotechnology Co., Ltd.;

[0056] γ-Methacryloxypropyltrimethoxysilane, model number 1228708, was purchased from Shanghai Haohong Biopharmaceutical Technology Co., Ltd.

[0057] Preparation of polyisocyanurate trimer: In parts by weight, 60 parts of polymerized MDI, 5 parts of trihydroxy polyether polyol and 10 parts of dihydroxy polyether polyol are mixed and stirred for 30 minutes, then 0.5 parts of Bronsted acid catalyst are added, and the mixture is placed under nitrogen atmosphere protection and reacted at 65°C for 2.5 hours to obtain an intermediate product; 60 parts of the intermediate product and 30 parts of hydroxy polyol are mixed for polymerization reaction (reaction temperature is 65°C, reaction time is 3 hours) to obtain a prepolymerization system; 40 parts of trihydroxy polyether polyol are added to 90 parts of the prepolymerization system for molding reaction (reaction temperature is 200°C, reaction time is 25 seconds) to obtain a polyisocyanurate trimer.

[0058] Preparation of modified basalt fiber: by weight, 4 parts of 2-aminoethyl diphenylborate were added to 150 parts of anhydrous ethanol, stirred for 30 minutes to obtain an impregnation solution, 60 parts of basalt fiber were added to the impregnation solution and treated for 3 hours, and then dried at 100° C. for 6 hours to obtain modified basalt fiber.

[0059] Preparation of modified aluminum nitride: Disperse 15 parts of aluminum nitride in 100 parts of anhydrous ethanol by weight, stir at a speed of 2000 r / min for 60 minutes, then add 8 parts of polymethyl methacrylate microspheres and 4 parts of γ-methacryloxypropyltrimethoxysilane and stir for 50 minutes, and filter to obtain a filter cake; transfer the filter cake to a muffle furnace, keep it warm at 150° C. for 60 minutes, and then calcine at 450° C. for 50 minutes to obtain modified aluminum nitride.

[0060] Example 1

[0061] This embodiment provides a method for preparing a fiber composite photovoltaic bracket material, comprising the following steps:

[0062] Step S1: adding 6 parts of polyisocyanurate trimer, 4 parts of modified aluminum nitride, 0.3 parts of coupling agent KH550, 0.8 parts of film-forming agent acrylic resin and 0.6 parts of lubricant hexadecyltrimethylammonium bromide to 95 parts of polyether type liquid polyurethane resin in parts by weight, stirring and mixing to obtain a mixture;

[0063] Step S2: Step S2: Pass 80 parts of modified basalt fibers through a mold, inject the mixture described in step S1 through a glue injection machine, heat to 190°C for curing and molding, then pultrude and cool to room temperature to obtain a fiber composite photovoltaic bracket material.

[0064] Example 2

[0065] This embodiment provides a method for preparing a fiber composite photovoltaic bracket material, comprising the following steps:

[0066] Step S1: adding 4 parts of polyisocyanurate trimer, 2 parts of modified aluminum nitride, 0.1 parts of coupling agent KH560, 0.5 parts of film-forming agent polyester polyurethane resin and 0.4 parts of lubricant hexadecyltrimethylammonium chloride to 85 parts of polyester liquid polyurethane resin in parts by weight, stirring and mixing to obtain a mixture;

[0067] Step S2: Pass 70 parts of modified basalt fibers through a mold, inject the mixture described in step S1 through a glue injection machine, heat to 200° C. for curing and molding, and then perform pultrusion molding and then cool to room temperature to obtain a fiber composite photovoltaic bracket material.

[0068] Example 3

[0069] This embodiment provides a method for preparing a fiber composite photovoltaic bracket material, comprising the following steps:

[0070] Step S1: adding 5 parts of polyisocyanurate trimer, 3 parts of modified aluminum nitride, 0.2 parts of coupling agent KH792, 0.6 parts of film-forming agent acrylic resin and 0.5 parts of lubricant octadecyltrimethylammonium chloride to 90 parts of oil ether type liquid polyurethane resin, by weight, and stirring and mixing to obtain a mixture;

[0071] Step S2: Pass 75 parts of modified basalt fibers through a mold, inject the mixture described in step S1 through a glue injection machine, heat to 195° C. for curing and molding, and then perform pultrusion molding and then cool to room temperature to obtain a fiber composite photovoltaic bracket material.

[0072] Comparative Example 1

[0073] This comparative example provides a method for preparing a photovoltaic bracket material, which differs from Example 1 in that commercially available polymeric MDI is used instead of polyisocyanurate trimer, commercially available basalt fiber is used instead of modified basalt fiber, and commercially available aluminum nitride is used instead of modified aluminum nitride.

[0074] Comparative Example 2

[0075] This comparative example provides a method for preparing a photovoltaic bracket material, which differs from comparative example 1 in that modified basalt fiber is used instead of commercially available basalt fiber.

[0076] Comparative Example 3

[0077] This comparative example provides a method for preparing a photovoltaic bracket material, which differs from comparative example 1 in that a polyisocyanurate trimer resin is used instead of commercially available polymeric MDI.

[0078] Comparative Example 4

[0079] This comparative example provides a method for preparing a photovoltaic bracket material, which differs from comparative example 1 in that modified aluminum nitride is used instead of commercially available aluminum nitride.

[0080] Comparative Example 5

[0081] This comparative example provides a method for preparing a photovoltaic support material, which differs from Example 1 in that commercially available polymeric MDI is used instead of polyisocyanurate trimer.

[0082] Comparative Example 6

[0083] This comparative example provides a method for preparing a photovoltaic bracket material, which differs from Example 1 in that commercially available basalt fibers are used to replace modified basalt fibers.

[0084] The performance of the photovoltaic support materials provided in the above embodiments and comparative examples was tested, and the testing method was as follows:

[0085] (1) Longitudinal tensile strength test: The test is carried out in accordance with the requirements of GB / T 31539-2015 Fiber reinforced composite pultruded profiles for structures.

[0086] (2) Flame retardancy test: Test according to the requirements of "T / CPIA 0013-2019 Photovoltaic Bracket".

[0087] (3) Thermal conductivity test: Test according to the requirements of GB / T 3139-2005 Test method for thermal conductivity of fiber reinforced plastics.

[0088] The above performance test data is shown in Table 1.

[0089] Table 1 Performance test results

[0090]

[0091] From the above content, it can be seen that the present invention uses modified basalt fiber as a composite reinforcing material, and then introduces polyisocyanurate trimer and modified aluminum nitride to prepare a fiber composite photovoltaic bracket material (Examples 1~3). The longitudinal tensile strength of the photovoltaic bracket material is 1130~1305MPa, the flame retardant grade is V-0, and the thermal conductivity is 0.91~0.98W / (m·K).

[0092] Compared with Example 1, commercially available polymeric MDI is used to replace polyisocyanurate trimer, commercially available basalt fiber is used to replace modified basalt fiber, and commercially available aluminum nitride is used to replace modified aluminum nitride, then the longitudinal tensile strength decreases, the flame retardancy decreases, and the thermal conductivity decreases (Comparative Example 1); compared with Comparative Example 1, modified basalt fiber is used to replace commercially available basalt fiber, and the longitudinal tensile strength is improved (Comparative Example 2); compared with Comparative Example 1, polyisocyanurate trimer is used to replace commercially available polymeric MDI, the longitudinal tensile strength is improved, and the flame retardancy is improved (Comparative Example 3); compared with Comparative Example 1, modified aluminum nitride is used to replace commercially available aluminum nitride, and the thermal conductivity increases (Comparative Example 4); compared with Example 1, commercially available polymeric MDI is used to replace polyisocyanurate trimer, the longitudinal tensile strength decreases, and the flame retardancy decreases (Comparative Example 5); compared with Example 1, commercially available basalt fiber is used to replace modified basalt fiber, the longitudinal tensile strength decreases, the flame retardancy decreases, and the thermal conductivity decreases (Comparative Example 6).

[0093] In summary, the present invention prepares a fiber composite photovoltaic bracket material by adding modified basalt fiber as a composite reinforcing material, and then introducing polyisocyanurate trimer and modified aluminum nitride. The bracket material has high longitudinal tensile strength and good flame retardant and thermal conductive properties.

Claims

1. A method for preparing a fiber composite photovoltaic bracket material, characterized in that: The following steps are involved: Step S1: adding 4 to 6 parts of polyisocyanurate trimer, 2 to 4 parts of aluminum nitride, 0.1 to 0.3 parts of coupling agent, 0.5 to 0.8 parts of film-forming agent and 0.4 to 0.6 parts of lubricant to 85 to 95 parts of liquid polyurethane resin, by weight, and stirring and mixing to obtain a mixture; Step S2: Pass 70 to 80 parts of basalt fibers through a mold, inject the mixture in step S1 through a glue injection machine, heat and solidify the mixture, and then pultrude and cool to room temperature to obtain a fiber composite photovoltaic bracket material; The preparation method of the polyisocyanurate trimer comprises: mixing 40-60 parts of polymeric MDI, 3-5 parts of trihydroxy polyether polyol and 5-10 parts of dihydroxy polyether polyol by weight for 20-30 minutes, then adding 0.3-0.5 parts of Bronsted acid catalyst, placing under nitrogen atmosphere protection, reacting at 55° C.-65° C. for 2-3 hours to obtain an intermediate product; mixing 40-60 parts of the intermediate product and 20-30 parts of hydroxy polyol for polymerization reaction to obtain a prepolymer system; adding 30-40 parts of trihydroxy polyether polyol to 60-90 parts of the prepolymer system for molding reaction to obtain a polyisocyanurate trimer; The basalt fiber is modified basalt fiber; The preparation method of the modified basalt fiber comprises: adding 2-4 parts of 2-aminoethyl diphenylborate to 120-150 parts of anhydrous ethanol by weight, stirring for 20-30 minutes to obtain an impregnation solution, adding 50-60 parts of basalt fiber to the impregnation solution for 2-3 hours, and then drying at 100-105° C. for 4-6 hours to obtain the modified basalt fiber; The aluminum nitride is modified aluminum nitride; The preparation method of the modified aluminum nitride comprises: dispersing 10 to 15 parts of aluminum nitride in 90 to 100 parts of anhydrous ethanol by weight, stirring at a speed of 1800 to 2000 r / min for 60 to 80 minutes, then adding 5 to 8 parts of polymethyl methacrylate microspheres and 2 to 4 parts of γ-methacryloxypropyltrimethoxysilane, stirring for 40 to 50 minutes, and filtering to obtain a filter cake; transferring the filter cake to a muffle furnace, keeping the temperature at 130 to 150° C. for 60 to 70 minutes, and then calcining at 450 to 500° C. for 40 to 50 minutes to obtain the modified aluminum nitride.

2. The method for preparing a fiber composite photovoltaic bracket material according to claim 1, characterized in that: The reaction temperature of the polymerization reaction is 55° C. to 65° C., and the reaction time is 2 to 3 hours.

3. The method for preparing a fiber composite photovoltaic bracket material according to claim 1, characterized in that: The reaction temperature of the molding reaction is 190-200° C., and the reaction time is 25-35 seconds.

4. The method for preparing a fiber composite photovoltaic bracket material according to claim 1, characterized in that: The liquid polyurethane resin is any one of a polyether type liquid polyurethane resin, a polyester type liquid polyurethane resin and an oil ether type liquid polyurethane resin, or a combination of at least two of them.

5. The method for preparing a fiber composite photovoltaic bracket material according to claim 1, characterized in that: The coupling agent is selected from any one of KH550 coupling agent, KH560 coupling agent and KH792 coupling agent or a combination of at least two thereof.

6. The method for preparing a fiber composite photovoltaic bracket material according to claim 1, characterized in that: The film-forming agent is acrylic resin or polyester polyurethane resin.

7. The method for preparing a fiber composite photovoltaic bracket material according to claim 1, characterized in that: The lubricant is selected from any one of cetyltrimethylammonium bromide, cetyltrimethylammonium chloride and octadecyltrimethylammonium chloride or a combination of at least two thereof.

8. The method for preparing a fiber composite photovoltaic bracket material according to claim 1, characterized in that: The conditions of the heating curing molding process include: a temperature of 190-200° C. and a time of 25-35 seconds.

Citation Information

Patent Citations

  • A fiber-reinforced unsaturated polyester resin composite material for photovoltaic support and preparation method thereof

    CN117603474B

  • Preparation method of aluminum nitride powder

    CN106744739A

  • Preparation method of basalt fiber composite photovoltaic support material

    CN118852851A